Design of a CSK-CDMA Based Indoor Visible Light Communication Transceiver using Raspberry Pi and LabVIEW - Khalid, Arslan; Saeed, Awais; Altaf, Zohair; Siddiqui, Abdul Rafay; Khan, Nesruminallah; Khan, Nesruminallah; Ali, Assad (International Journal of Integrated Engineering, 2019)
Visible Light Communication (VLC) has drastically drawn the attention of both academia and industry as it can offer simultaneous lighting and data communication in an indoor environment. Additionally, VLC also tender a viable means to assuage the radio spectrum crunch. However, the data rate of the VLC system is choked because of the limited modulation bandwidth of Light Emitting Diode (LED), baseband modules, and intersymbol interference (ISI). In this article, an indoor VLC based software-defined radio (SDR) is designed and implemented that make use of Color Shift Keying (CSK) modulation, Code Division Multiple Access (CDMA) technique, and Raspberry Pi (RPi) to enabled the ISI free high data rate communication. The SDR is designed in LabVIEW software interfaced with the MATLAB and tested for text transmission. Numerous experiments were conducted on SDR at different alignments of transmitter and receiver. Our findings through experimentation showed that the SDR delivers an improved data rate of 2.645Mbps. Over and above, MATLAB based simulation packages are also conceived that validate the effectiveness of the proposed CSK-CDMA based VLC system. The bit-error-rate (BER) results of the proposed system are compared with the traditional CSK-OOK based VLC system. The results are quite impressive and show remarkable coding gain.